2009
DOI: 10.1017/s1751731109990711
|View full text |Cite
|
Sign up to set email alerts
|

Light lamb meat quality packed under modified atmospheres: effect of stunning systems (electrically v. gas)

Abstract: In the present study, the effect of type of stunning (electrical v. gas) and the gas mixtures in a modified atmosphere (MA) packing system (MA-A: 30% CO 2 1 70% O 2 ; MA-B: 30% CO 2 1 69.3% N 2 1 0.7% CO; MA-C: 40% CO 2 1 60% N 2 ) on light lamb meat quality, obtained by 20 males of Manchego Spanish breed, was evaluated at 7, 14 and 21 days post packing. For all ageing times, gas-stunned groups reached the highest pH ( P , 0.001) and shear force (SF) values (P , 0.05), and at 21 days, water losses were highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The optimum colour stability of packaged red meat is obtained by using a mixture of gases with high concentrations of oxygen and low proportions of carbon dioxide (Linares and Vergara, 2009). The carbon dioxide in the package atmosphere restricts the growth of aerobic spoilage bacteria (Gill, 1991), whereas a high oxygen concentration increases lipid oxidation, which adversely affects the flavour and nutritional value of the meat.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum colour stability of packaged red meat is obtained by using a mixture of gases with high concentrations of oxygen and low proportions of carbon dioxide (Linares and Vergara, 2009). The carbon dioxide in the package atmosphere restricts the growth of aerobic spoilage bacteria (Gill, 1991), whereas a high oxygen concentration increases lipid oxidation, which adversely affects the flavour and nutritional value of the meat.…”
Section: Introductionmentioning
confidence: 99%
“…The use of gases such as oxygen allows the maintenance of the red colour on the surface of meat whereas carbon dioxide inhibits the growth of microorganisms (Š četar et al 2010;McMillin 2017). Modified atmosphere packaging (MAP) with 60-80% O 2 and 40-20% CO 2 , is the most usual gas mixture used in red raw meat (Linares and Vergara 2009). McMillin (2008) reported that the inclusion of 20-30% CO 2 prolongs the shelf life by inhibiting bacterial growth and Š četar et al (2010) stated that CO 2 proportion should not be higher than 20% in order to achieve a maximal inhibition of aerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%